A study of rubella haemagglutination inhibition antibodies in rheumatoid arthritis - Kacaki, J. N. (1970)
In the literature there are speculations concerning a possible role of Rubella virus in the etiopathogenesis of rheumatoid arthritis (RA). Rubella haemagglutination inhibition (RHI) antibody titres were determined in sera from thirty-six pairs of patients with RA and diseases unrelated to RA, matched for age and sex. Latex flocculation tests (LFT) were performed in both groups, as well. Mean ranks (log(2)) of RHI test for the RA and non-RA groups were almost identical (5·75 and 5·94, respectively). Titre of RHI was unrelated to the presence or absence, or titre, of LFT. Thus, no evidence of continuing Rubella virus infection can be found in patients with RA by this antibody test. The possibility that the aetiology of RA may be related to some viral infection is nevertheless of continuing interest.